2018
DOI: 10.1007/s00572-018-0844-x
|View full text |Cite
|
Sign up to set email alerts
|

Appropriate nonmycorrhizal controls in arbuscular mycorrhiza research: a microbiome perspective

Abstract: Establishment of nonmycorrhizal controls is a "classic and recurrent theme" in mycorrhizal research. For decades, authors reported mycorrhizal plant growth/nutrition as compared to various nonmycorrhizal controls. In such studies, uncertainties remain about which nonmycorrhizal controls are most appropriate and, in particular, what effects the control inoculations have on substrate and root microbiomes. Here, different types of control and mycorrhizal inoculations were compared with respect to plant growth and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 48 publications
1
28
0
Order By: Relevance
“…When interpreting the observed growth depression in the mycorrhizal treatment, we also need to remember that it is virtually impossible to produce nonmycorrhizal controls with identical composition of microbial communities as in the mycorrhizal treatment (Gryndler et al., ). We therefore cannot completely rule out two alternative explanations considering possible differences in the composition of non‐AMF microbial communities in both inoculation treatments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When interpreting the observed growth depression in the mycorrhizal treatment, we also need to remember that it is virtually impossible to produce nonmycorrhizal controls with identical composition of microbial communities as in the mycorrhizal treatment (Gryndler et al., ). We therefore cannot completely rule out two alternative explanations considering possible differences in the composition of non‐AMF microbial communities in both inoculation treatments.…”
Section: Discussionmentioning
confidence: 99%
“…The filtrate was prepared by filtration of a nonsterile soil suspension (1:10, w/v, 60 s homogenization by immersion blender, 1 h on a reciprocal shaker) through filter paper with a pore size of 15 μm to remove AMF propagules. We are aware that this approach does not allow separating organisms of similar or larger size than AMF spores such as representatives of micro‐ and mesofauna (Wagg et al., ); nevertheless, despite many efforts, there does not seem to be a way to establish a nonsterile cultivation experiment in which the treatments differ only by the presence of mycorrhizal fungi (Gryndler et al., ). Plants were cultivated in the greenhouse under natural daylight conditions, positioned randomly on the bench, and watered with distilled water to saturation as required.…”
Section: Methodsmentioning
confidence: 99%
“…Mycorrhizal inoculum was obtained from pot culture of an AM fungus Rhizophagus irregularis strain SYM5 (described in Gryndler et al 2018), which was produced in the glasshouse for 8 months prior to the experiments described here, with leek ( Allium porrum ) as a host plant. Leek roots from the inoculum pots were harvested and cut mechanically into small pieces (< 1 cm) and then mixed back into the potting substrate from the inoculum production pots (which was the same as the potting substrate used in the experiments described here).…”
Section: Methodsmentioning
confidence: 99%
“…Although previous studies have shown that the diversity of belowground mutualists can relax plant competition, these studies used fungal mutualists from the same functional group (AM fungi only) and plants of different functional groups (Wagg et al 2011a, b). We reiterate that our experimental design did not allow for disentangling the effects of other soil microorganisms that could have been present in our mycorrhizal inoculum, however, a recent study pointed that no proper control is feasible when using complex mycorrhizal inoculum (Gryndler et al 2018). Nevertheless, we highlight that the effect of fungal-fungal interactions on plant communities are likely to be moderated by the functional identity of mutualist fungi and how they form partnerships with the co-occurring closely-related plants.…”
Section: Generamentioning
confidence: 95%